Characteristics and genesis of the polygonal fault system in southern slope of the Qiongdongnan Basin, South China Sea. (February 2016) - Han, Jianhui; Leng, Jigao; Wang, Yingmin
Abstract: Based on 3D seismic data, the polygonal fault system (PFS) discovered in the southern slope of the Qiongdongnan (QDN) Basin was studied through fine seismic interpretation and coherent cube analysis. The results show that: ① the PFS is mostly composed of small plate-type faults, with fault length of 1–3 km, maximum fault throw of 20–40 m and dip angle of 25°–45°; ② the PFS is mainly observed in the Huangliu Formation, deposited in the early stage of fast slope depression; ③ the PFS is layer-bound and can be separated into two tiers by T31′ interface with obvious channel incision features; ④ the PF of tier2 exhibit "y" structural style, including two parallel faults, master fault and associated fault, dipping in opposite directions. Their intersection relationship can be divided into three classes, and 14 sub-classes based on the fault intersection relationship of master fault and its associated fault; ⑤ the PFS is dominated by two strikes: NE60° and NW150°, indicating that it was controlled by tensile stress produced by differential settlement between the Xisha uplift and QDN basin; and ⑥ its genesis was jointly controlled by the syneresis of clay minerals and overpressure cyclical dehydration. Highlights: The polygonal faults (PF) are controlled by the interface marked by incised channels. Most big PF are associated by a small parallel fault, dipping in opposite directions. The PF strikes may controlled by tensile stress produced by differential settlement. The PF mechanisms include clay mineral synersis and overpressure. PF may act as hydrocarbon migration pathways in hydrocarbon expulsion.